Economic evaluation in the field of mental health: conceptual basis - Ana Flávia Barros da Silva Lima; Luciane Nascimento Cruz; Carisi Anne Polanczyk; Carlos Renato Moreira Maia (Brazilian Journal of Psychiatry, 2013)
Objective: Technological advances in medicine have given rise to a dilemma concerning the use of new health technologies in a context of limited financial resources. In the field of psychiatry, health economic evaluation is a recent method that can assist in choosing interventions with different cost and/or effectiveness for specific populations or conditions. This article introduces clinicians to the fundamental concepts required for critical assessment of health economic evaluations. Methods: The authors conducted a review with systematic methods to assess the essential theoretical framework of health economic evaluation and mental health in Brazil through textbooks and studies indexed in the PubMed, Cochrane Central, LILACS, NHS CRD, and REBRATS databases. A total of 334 studies were found using the specified terms (MeSH - Mental Health AND Economic, Medical) and filters (Brazil AND Humans); however, only five Brazilian economic evaluations were found. Results and conclusions: Economic evaluation studies are growing exponentially in the medical literature. Publications focusing on health economics as applied to psychiatry are increasingly common, but Brazilian data are still very incipient. In a country where financial resources are so scarce, economic analyses are necessary to ensure better use of public resources and wider population access to effective health technologies.